The Influence Of Entrepreneurial Knowledge, Entrepreneurial Characteristics And Entrepreneurial Competencies On The Success Of MSMES Taba Jambu Village In Central Bengkulu - Fadhilah, Nurul Tri; Tawakal, Anzori; Yanti, Rina Trisna (Journal of Management, Economic, and Accounting, 2025)
This study aims to determine the effect of entrepreneurial knowledge, entrepreneurial characteristics and entrepreneurial competence on business success in MSMEs in Taba Jambu Village in Central Bengkulu. This type of research is a type of quantitative research. The data collection method in this study used a questionnaire technique, with a sample of 40 respondents. The results showed that multiple linear regression Y = 4,092 + 0.251 X1 + 0.472 X2 + 0.367 X3 + 1,455. Where the coefficient is positive, it means that there is a positive or unidirectional correlation between the variables of Entrepreneurial Knowledge (XI), Entrepreneurial Characteristics (X2), Entrepreneurial Competence (X3), the value is 0 (zero), then the success (Y) of MSMEs in Taba Jambu Village, Central Bengkulu. The results showed that the entrepreneurial knowledge test (XI) showed tcount 3.441> ttable 1.683 and sigfinication 0.001 <0.05, then the results of the hypothesis Ha is accepted and Ho is rejected, meaning that entrepreneurial knowledge has a positive and significant effect on the success (Y) MSMEs Taba Jambu Village in Central Bengkulu. The results showed that the entrepreneurial characteristics test (X2) showed tcount 3.614> t table 1.683 and sigfinication 0.001 <0.05, then the results of the hypothesis Ha is accepted and Ho is rejected, meaning that entrepreneurial knowledge has a positive and significant effect on the success (Y) of MSMEs Taba Jambu Village in Central Bengkulu. The results showed that the entrepreneurial competency test (X3) showed tcount 2.761> ttable 1.683 and sigfinication 0.009 <0.05, then the results of the hypothesis Ha is accepted and Ho is rejected, meaning that entrepreneurial knowledge has a positive and significant effect on the success (Y) of MSMEs Taba Jambu Village in Central Bengkulu. Based on the comparison of the Fcount value with Ftable, the Fcount value is greater than the Ftable value, namely 41.089> 2.61, it is concluded that Accepting the Hypothesis, meaning that there is a simultaneous influence between Entrepreneurial Knowledge (XI), Entrepreneurial Characteristics (X2), Entrepreneurial Competence (X3) on the Success (Y) of MSMEs Taba Jambu Village in Central Bengkulu. This can be seen at a significance level of 0.000 <0.05